The Resistance to Adopting Online Marketplace: The Influence of Perceived Risk and Behavioral Control of Small and Medium Enterprises in Indonesia - Dwipuspa Ramadhanti Santoso; Putu Wuri Handayani; Fatimah Azzahro (Bina Nusantara University, 2022)
To date, the number of e-commerce applications in Indonesia keeps increasing. However, the adoption rate amongst Small and Medium Enterprises (SMEs) is still around 13%. Thus, the research aims to analyze the factors that affect small and medium enterprises’ resistance to adopting online marketplaces in Indonesia by applying the technological-organizationalenvironmental framework, the diffusion of innovations theory, and the innovation resistance model. The respondents are 356 owners of SMEs in Indonesia who have sold their products online through social media or marketplace. The research applies a quantitative approach using an online questionnaire and interview. Then, the covariance-based structural equation modeling method is applied to analyze the data. In addition, the research interviews five SME representatives to gain further understanding and information for the rejected hypothesis. The results show that perceived complexity, owners’ self-efficacy, and enabling conditions are proven to affect perceived behavioral control. Perceived complexity is also shown to affect perceived risk. On the other hand, government support does not affect perceived behavioral control. It is also found that perceived risk and behavioral control affect resistance to adopting online marketplaces. The findings provide recommendations to overcome this situation, such as the simplification of online marketplace features for sellers and improvements in the digital literacy of the owners of SMEs.